Evaluación de tres soluciones Hidropónicas comerciales en la Producción de dos Asociaciones de Forraje Verde Hidropónico (fvh) como alternativa de transferencia de Tecnología, Latacunga, 2015. - Larrea Miranda, Ricardo Andres (2016)
2015" was held in the Campus Salache of the Technical University of Cotopaxi, located in the province of Cotopaxi, Parish Eloy Alfaro, sector Salache Bajo, where two associations of forages (vetch - barley and ryegrass - barley) were tested, three solutions (Evergreen 0,01 ccm-2, Kelpak 0,05 ccm-2 y Poliverdol 0,01 ccm-2) and three irrigation frequencies (3, 4 and 5 times per day) with 18 treatments and three repetitions, indicators evaluated were: percentage of germination, plant height (m), days to harvest, weight forage harvest (kg) and performance (kgm-2); the main results were: for the germination percentage .................. .., for the variable plant height S3 solution obtained 0.18 m average, for days to harvest there were no significant differences, being the averages of all studied factors 16.33; the variable weight in forage harvest, the best solution was to S3 (4.14 kg), the best interactions were A1S3 (4.64 kg) and A1F3 (4.24 kg); for the performance, the main averages obtainec were for S3 (3.72 kgm-2) and for the interactions, A1S3 (4.18 kgm-2), A1F3 (3.82 kgm-2) and the best irrigation frequency was F2 ( 3.5 kgm-2). It is concluded that Vicia and Cebada were the best forage association wich presented optimal averages , the best solution was Poliverdol 0.01 ccm-2 , and irrigation frequency that is needed is F2 (4 timesdaily) .